Confirm Not Command: examining Fraudsters’ Use of Language to Compel Victim Compliance in Their Own Exploitation - Carter, Elisabeth (The British journal of criminology, 2023)
Using discourse analysis to examine exchanges between fraudsters and victims in telephone-mediated frauds, this research examines the interactional techniques used by perpetrators of fraud to gain and maintain compliance from their victims, without causing them alarm. It reveals how compliance is secured and maintained in a process of establishing the relationship, grooming the victim and setting expectations of follow-through. Reimagining traditional understandings of fraud victimization and vulnerability, this work exposes how social and interactional norms are replicated and manipulated by fraudsters in order to compel individuals to be drawn into participating in an alternate, exploitative reality that is indistinguishable from safety; quashing a victim’s ability to recognize the situation as harmful and rendering any motivation to escape as nonsensical. In doing so, this paper questions the efficacy of public fraud protection guidance strategies and delivers evidence for the need to change the present approach to understanding and tackling fraud victimization and complicity.